Aplicativo para smartphone destinado à medição da irregularidade longitudinal em rodovias - Almeida, Lucas Cavalcante de (2018)
Many equipment is being developed to measure or estimate the longitudinal unevenness of the pavements. It is known that values above the limits established for this parameter contribute negatively to the functional condition of the pavements, damaging the rolling quality, increasing the Vehicle Operating Costs (VOC) and reducing the useful life of the pavement. Due to the importance of the study of this pathology, this work proposes the development of a smartphone application, called SmartIRI, to estimate the International Roughness Index (IRI), the parameter that better represents the longitudinal irregularity of flexible pavements. The proposed tool is loaded onto a vehicle by means of a bracket attached to the windshield and is based on the use of sensors present in smartphones, such as the accelerometer and the Global Positioning System (GPS), to obtain the data of vertical acceleration, speed and location. The data from the accelerometer and the GPS receiver were processed in order to inform the user of the IRI georeferenced in real time. The tests obtained after a distance of 165 km showed that the calculated IRI values presented satisfactory correlation with data provided by another application whose proposal is the measurement of longitudinal irregularity by measurements of the laser profilometer by subjective analysis using the Current Service Value (VSA), and by the Level and Rod method. Among the multiple uses of measurements of longitudinal irregularity, SmartIRI was used as a tool to control the quality of execution of patches and rigid pavements, presenting itself as an alternative to traditional surveys. It was found that the use of the developed application can be a viable alternative, especially in places where there are few financial, material or professional resources for this purpose and, especially, when applied at the network level.